Perspectives for crime prevention (Academic Journal of Internal Affairs, 2019)
In the 21st century crime prevention will be gentrified as the traditional means of criminal law and criminal policy are not able any more to handle criminality and therefore the focus will be laid on crime prevention. The increasing challenges of globalisation cannot be handled by law enforcement measures, the solution can be a prophylaxis-based society. The author presents how crime prevention gains a new dimension int the 21st century.
Keywords: crime prevention; new dimension; 21st century